An environment-friendly treatment process for surface corrosion-resistant zinc infiltration of mine supporting anchor rods
Patent Information
- Application Number
- CN202611292280.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-25
- Publication Date
- 2026-10-09
AI Technical Summary
该类传统方法虽能在一定程度上赋予锚杆耐腐蚀性能,但存在诸多难以克服的技术缺陷与环保问题
第一,关于稀土催渗剂的协同作用机理。本发明采用氯化铈与氯化镧的混合物作为稀土催渗剂,并控制二者质量比为1:0.5-2。铈和镧虽同属轻稀土,但原子半径存在差异,铈约为0.182nm,镧约为0.188nm。在渗锌温度下,两种稀土原子在基体表面晶界处偏聚时,因半径不同而引发不同程度的晶格畸变,形成更为多样的扩散通道,相比于单一稀土元素,能为锌原子的扩散提供更丰富的低能垒路径。同时,该比例范围确保了两种稀土元素在晶界的偏聚密度适中,避免因某一元素过量偏聚造成局部过度畸变而阻碍扩散。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of zinc diffusion process technology, specifically, it relates to an environmentally friendly zinc diffusion process for corrosion-resistant and anti-corrosion treatment of the surface of mining support anchor bolts. Background Technology
[0002] In existing anti-corrosion treatment technologies for mine support anchor bolts, the commonly used process route is pickling and rust removal + hot-dip galvanizing or electro-galvanizing + chromate passivation. While this traditional method can impart corrosion resistance to anchor bolts to a certain extent, it suffers from numerous insurmountable technical defects and environmental problems. First, the pre-pickling process generates large amounts of wastewater and acid mist containing acid and heavy metal ions, posing serious hazards to the environment and the health of operators. Furthermore, pickling easily leads to hydrogen embrittlement of the substrate, affecting the mechanical safety of the anchor bolt. Second, conventional hot-dip galvanizing or electro-galvanizing layers are mostly mechanically bonded to the substrate, resulting in limited interfacial bonding strength. Under complex stress conditions underground, the coating is prone to peeling, and once corrosive media penetrate, it spreads rapidly, failing to meet the long-term support requirements of mines. Third, the chromate passivation post-treatment, widely used to improve corrosion resistance, introduces toxic and harmful substances such as hexavalent chromium. Its carcinogenicity and bioaccumulation have been strictly limited, failing to meet the increasingly stringent environmental regulations and green mine construction requirements. In addition, although some existing zinc diffusion processes use a single rare earth element (such as adding cerium or lanthanum alone) for catalytic diffusion, the catalytic effect is limited. High zinc diffusion temperatures (usually not lower than 450℃) or extended holding times are often required to obtain an effective diffusion layer thickness. This not only increases energy consumption but also easily leads to matrix grain growth and decreased mechanical properties. Furthermore, the uniformity and density of the diffusion layer are still insufficient, limiting the potential for improving corrosion resistance.
[0003] Therefore, developing an environmentally friendly anchor bolt surface treatment method that can completely eliminate pickling and chromating processes, achieve low-temperature and high-efficiency zinc diffusion, and significantly improve the quality and corrosion resistance of the diffusion layer has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art and provide an environmentally friendly treatment process for corrosion-resistant zinc infiltration on the surface of mining support anchor bolts.
[0005] The objective of this invention can be achieved through the following technical solutions: An environmentally friendly zinc-plating treatment process for corrosion-resistant and anti-corrosion treatment of the surface of mining support anchor bolts includes the following steps: (1) The surface of the mining support anchor rod is subjected to acid-free mechanical rust removal treatment so that the surface cleanliness reaches Sa2.5 or above and the roughness Rz is controlled at 25-75 μm; (2) After the rust removal treatment, the anchor rod is mixed with the chromium-free rare earth penetration agent and then placed in a sealed zinc penetration container. The chromium-free rare earth penetration agent is composed of the following components by mass percentage: 85%-95% zinc powder, 1%-4% activator, 3%-11% anti-caking agent, and 0.5%-2% rare earth penetration agent. The rare earth penetration agent is a mixture of cerium chloride and lanthanum chloride, wherein the mass ratio of cerium chloride to lanthanum chloride is 1:(0.5-2). (3) The zinc diffusion container is heated at a temperature of 340-440℃ and rotated continuously for 2-6 hours to make the anchor rod fully contact the zinc diffusion agent and form a zinc-iron alloy diffusion layer on the surface of the anchor rod. (4) After zinc diffusion is completed, cool to room temperature, separate the anchor rod from the residual zinc diffusion agent, and dry clean the surface of the anchor rod to obtain a mining support anchor rod with a corrosion-resistant zinc diffusion layer.
[0006] This invention replaces the traditional chromium-containing passivation process with a chromium-free zinc penetration agent formula, eliminating pickling and the introduction of chromium compounds throughout the entire process, thus eliminating pickling wastewater and chromium ion pollution at the source and achieving truly environmentally friendly production.
[0007] In this invention, the rare earth penetration catalyst is a mixture of cerium chloride and lanthanum chloride. The two work synergistically in a specific ratio, which is the key innovation of this invention to achieve low-temperature and high-efficiency zinc penetration.
[0008] Cerium and lanthanum are both light rare earth elements with similar chemical reactivity, but their atomic radii differ: cerium's atomic radius is approximately 0.182 nm, while lanthanum's is approximately 0.188 nm. At zinc diffusion temperatures, cerium chloride and lanthanum chloride gradually decompose, and the precipitated active cerium and lanthanum atoms preferentially accumulate along the matrix surface and grain boundaries. Due to the difference in atomic radii between the two rare earth elements, their segregation at grain boundaries can induce different types of lattice distortions, forming a more complex stress field distribution. This provides a richer network of fast diffusion pathways for zinc atoms, and compared to single rare earth elements, the effect of mixed rare earth elements on reducing diffusion activation energy is more significant.
[0009] When the mass ratio of cerium chloride to lanthanum chloride is controlled within the range of 1:0.5-2, the aforementioned synergistic effect of the two rare earth elements reaches its optimal balance. If this ratio is greater than 1:0.5, i.e., the amount of lanthanum chloride is too low, the large radius distortion effect brought by lanthanum atoms is insufficient, the diversity of grain boundary diffusion channels decreases, the infiltration effect approaches that of cerium chloride alone, and the improvement in zinc infiltration efficiency is limited. If this ratio is less than 1:2, i.e., the amount of lanthanum chloride is too high, due to the larger atomic radius of lanthanum, excessive agglomeration causes excessive distortion of the grain structure, which in turn hinders the orderly diffusion of zinc atoms, leading to a decrease in the uniformity of the infiltrated layer. This invention precisely limits the mass ratio of cerium chloride to lanthanum chloride to 1:0.5-2, which can construct a diffusion channel network with suitable density and distribution in the grain boundary region of the substrate surface, ensuring uniform thickness and dense structure of the infiltrated layer while reducing the zinc infiltration temperature or shortening the holding time.
[0010] The total amount of rare earth penetration catalyst added should be controlled between 0.5% and 2% of the total mass of zinc penetration agent. When the addition amount is less than 0.5%, the number of active rare earth atoms is insufficient to form effective grain boundary segregation on the matrix surface, and the penetration effect is not obvious. When the addition amount is greater than 2%, excessive rare earth chloride decomposition products accumulate in the zinc penetration agent, which will affect the fluidity and reusability of the zinc penetration agent, and the marginal increase in penetration effect will decrease significantly.
[0011] In a more optimized manner, the mechanical rust removal in step (1) is sandblasting or shot blasting, and the process is carried out in a fully enclosed negative pressure dust removal system.
[0012] In a more optimized manner, the activator in step (2) is ammonium chloride, and the anti-caking agent is aluminum oxide.
[0013] Ideally, the zinc powder in step (2) has a particle size of 200-400 mesh and a purity of not less than 99%.
[0014] In a more optimized manner, the heating rate in step (3) is 5-10℃ / min and the container rotation speed is 3-8r / min.
[0015] More optimally, the dry cleaning described in step (4) involves blowing with compressed air and then applying a polishing brush.
[0016] Ideally, the base material of the mining support anchor is Q235, Q345, 20MnSi or 25MnSi steel.
[0017] Ideally, the thickness of the zinc-impregnated anti-corrosion layer is 25-80 μm.
[0018] The beneficial effects of this invention are: First, regarding the synergistic mechanism of rare earth diffusion catalysts. This invention uses a mixture of cerium chloride and lanthanum chloride as a rare earth diffusion catalyst, controlling the mass ratio of the two to be 1:0.5-2. Although cerium and lanthanum both belong to light rare earths, their atomic radii differ; cerium is approximately 0.182 nm, and lanthanum is approximately 0.188 nm. At the zinc diffusion temperature, when the two rare earth atoms segregate at the grain boundaries on the matrix surface, the difference in radii induces varying degrees of lattice distortion, forming more diverse diffusion channels. Compared to a single rare earth element, this provides richer low-barrier pathways for zinc atom diffusion. Simultaneously, this ratio range ensures a moderate segregation density of the two rare earth elements at the grain boundaries, avoiding excessive local distortion caused by excessive segregation of one element, which would hinder diffusion.
[0019] Secondly, regarding the improvement of the zinc diffusion layer structure, rare earth elements segregate at grain boundaries during zinc diffusion, inhibiting grain growth and refining the grain structure, thus increasing the density of the zinc diffusion layer. According to basic metallurgical principles, grain refinement improves material hardness, and a denser diffusion layer reduces the penetration channels of corrosive media, positively impacting corrosion resistance.
[0020] Third, regarding environmental protection. This invention uses acid-free mechanical rust removal to replace traditional pickling pretreatment, generating no pickling wastewater; it uses chromium-free zinc penetration agent to replace chromium-containing passivating agent, eliminating heavy metal pollution such as chromium, nickel, and lead; and the post-treatment uses dry cleaning, resulting in no process wastewater discharge. The entire process achieves environmentally friendly production from source to end. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1: This embodiment provides an environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts. The base material of the mine support anchor bolt is Q235 steel. The specific steps are as follows: (1) Mechanical rust removal: The anchor bolt surface is treated by sandblasting. The abrasive is cast steel shot, the sandblasting pressure is 0.6MPa, the spraying distance is 180mm, and the treatment process is carried out in a fully enclosed negative pressure dust removal system. After treatment, the surface cleanliness reaches Sa2.5 level, and the roughness Rz is controlled at 40-60μm. (2) Zinc infiltration agent formulation: The chromium-free rare earth zinc infiltration agent is formulated according to the following mass percentages: 90% zinc powder, 2.5% ammonium chloride activator, 6.5% alumina anti-caking agent, and 1.0% rare earth infiltration agent. Among them, the zinc powder has a particle size of 300 mesh and a purity of 99.5%; the rare earth infiltration agent is a mixture of cerium chloride and lanthanum chloride with a mass ratio of 1:1. All components are thoroughly mixed before use. (3) Loading and zinc diffusion treatment: The anchor rod treated in step (1) and the zinc diffusion agent prepared in step (2) are loaded into a sealed zinc diffusion container at a volume ratio of 1:2. The zinc diffusion container is heated at a heating rate of 8℃ / min. After heating to 400℃, it is kept at the temperature for 4 hours. During this period, the container is continuously rotated at a speed of 5r / min to ensure that the anchor rod and the zinc diffusion agent are in full contact and to form a zinc-iron alloy diffusion layer on the surface of the anchor rod. (4) Cooling and post-treatment: After zinc diffusion is completed, the container is naturally cooled to room temperature, the anchor rod and residual zinc diffusion agent are separated, the surface of the anchor rod is dry-cleaned by blowing with compressed air and polishing with a polishing brush, and a mining support anchor rod with a corrosion-resistant zinc diffusion layer is obtained; the thickness of the obtained zinc diffusion anti-corrosion layer is 55m.
[0023] Example 2: This embodiment provides an environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts. The base material of the mine support anchor bolt is Q235 steel. The specific steps are as follows: (1) Mechanical rust removal: The surface of the anchor rod is treated by shot blasting. The abrasive used in the shot blasting is cast steel shot. The treatment process is carried out in a fully enclosed negative pressure dust removal system. After treatment, the surface cleanliness reaches Sa2.5 level and the roughness Rz is controlled at 30-55 μm. (2) Zinc infiltration agent formulation: The chromium-free rare earth zinc infiltration agent is formulated according to the following mass percentages: 95% zinc powder, 1.0% ammonium chloride activator, 3.5% alumina anti-caking agent, and 0.5% rare earth infiltration agent. The zinc powder has a particle size of 400 mesh and a purity of 99.5%. The rare earth infiltration agent is a mixture of cerium chloride and lanthanum chloride in a mass ratio of 1:2. All components are thoroughly mixed before use. (3) Loading and zinc diffusion treatment: The anchor rod treated in step (1) and the zinc diffusion agent prepared in step (2) are loaded into a sealed zinc diffusion container at a volume ratio of 1:2. The zinc diffusion container is heated at a heating rate of 5℃ / min. After heating to 340℃, it is kept at the temperature for 6 hours. During this period, the container is continuously rotated at a speed of 3r / min to ensure that the anchor rod and the zinc diffusion agent are in full contact and to form a zinc-iron alloy diffusion layer on the surface of the anchor rod. (4) Cooling and post-treatment: Same as step (4) in Example 1; the thickness of the resulting zinc-impregnated anti-corrosion layer is 45 μm.
[0024] Example 3: This embodiment provides an environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts. The base material of the mine support anchor bolt is Q235 steel. The specific steps are as follows: (1) Mechanical rust removal: The anchor bolt surface is treated by sandblasting. The abrasive is cast steel shot, the sandblasting pressure is 0.5MPa, the spraying distance is 200mm, and the treatment process is carried out in a fully enclosed negative pressure dust removal system. After treatment, the surface cleanliness reaches Sa2.5 level, and the roughness Rz is controlled at 50-75μm. (2) Zinc infiltration agent formulation: The chromium-free rare earth zinc infiltration agent is formulated according to the following mass percentages: 85% zinc powder, 4.0% ammonium chloride activator, 9.0% alumina anti-caking agent, and 2.0% rare earth infiltration agent. Among them, the zinc powder has a particle size of 200 mesh and a purity of 99.0%; the rare earth infiltration agent is a mixture of cerium chloride and lanthanum chloride with a mass ratio of 1:0.5. All components are thoroughly mixed before use. (3) Loading and zinc diffusion treatment: The anchor rod treated in step (1) and the zinc diffusion agent prepared in step (2) are loaded into a sealed zinc diffusion container at a volume ratio of 1:2. The zinc diffusion container is heated at a heating rate of 10℃ / min. After heating to 440℃, it is kept at the temperature for 2 hours. During this period, the container is continuously rotated at a speed of 8r / min to ensure that the anchor rod and the zinc diffusion agent are in full contact and to form a zinc-iron alloy diffusion layer on the surface of the anchor rod. (4) Cooling and post-treatment: Same as step (4) in Example 1; the thickness of the resulting zinc-impregnated anti-corrosion layer is 48 μm.
[0025] Comparative Example 1: This comparative example provides a zinc penetration anti-corrosion treatment process for the surface of a mining support anchor rod. The steps are basically the same as those in Example 1, except that: in step (2), no rare earth penetration agent is added to the zinc penetration agent. The zinc penetration agent consists of 91% zinc powder, 2.5% ammonium chloride activator, and 6.5% alumina anti-caking agent. The thickness of the resulting zinc penetration anti-corrosion layer is 38 μm.
[0026] Comparative Example 2: This comparative example provides a zinc penetration anti-corrosion treatment process for the surface of a mining support anchor rod. The steps are basically the same as those in Example 1, except that: the rare earth penetration agent in step (2) is only cerium chloride and does not contain lanthanum chloride. The amount of rare earth penetration agent added is still 1.0%; the thickness of the obtained zinc penetration anti-corrosion layer is 47m.
[0027] Comparative Example 3: This comparative example provides a zinc penetration anti-corrosion treatment process for the surface of a mining support anchor rod. The steps are basically the same as those in Example 1, except that: the rare earth penetration agent in step (2) is only lanthanum chloride and does not contain cerium chloride. The amount of rare earth penetration agent added is still 1.0%; the thickness of the resulting zinc penetration anti-corrosion layer is 44 μm.
[0028] Testing experiment: (1) Using a Vickers hardness tester, with a load of 100g and a holding time of 15s, five points were randomly selected on the surface of the anchor rod for measurement, and the arithmetic mean was taken. (2) Referring to GB / T 10125, a 5% sodium chloride solution with a pH value of 6.5-7.2 and a test temperature of 35℃ was used for continuous spraying. The time for red rust to appear on the sample surface was used as the evaluation index for corrosion resistance. The obtained data is shown in the table below: project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Surface hardness / HV 310 298 325 256 275 270 Time to red rust appearance / h 1254 1078 1123 724 967 923 Conclusion: In summary, the corrosion-resistant zinc-infiltrating anti-corrosion and environmentally friendly treatment method for the surface of mining support anchor bolts proposed in this invention significantly improves the performance of the zinc-infiltrating layer while achieving environmentally friendly production through the use of acid-free mechanical rust removal, chromium-free rare earth infiltrating agents, and a full-process dry cleaning. The comparative data from the examples and comparative examples clearly show that: Comparative Example 1, without the addition of rare earth infiltrating agents, has a zinc-infiltrating layer hardness of only 256 HV and a red rust appearance time of only 724 hours, far lower than the examples; while Comparative Examples 2 and 3, using cerium chloride or lanthanum chloride alone, show improved hardness and corrosion resistance time compared to Comparative Example 1, but still fall short of the three examples. In Examples 1 to 3, due to the synergistic effect of cerium chloride and lanthanum chloride at a mass ratio of 1:0.5-2, the difference in radii between the two rare earth atoms induces different types of lattice distortion at the grain boundaries, constructing richer diffusion channels. This results in a denser and more uniform infiltration layer, with hardnesses reaching 310 HV, 298 HV, and 325 HV, respectively, and resistance to neutral salt spray corrosion reaching 1254 h, 1078 h, and 1123 h, respectively, all significantly superior to the comparative examples. Example 1 achieved the best corrosion resistance under moderate proportions and process conditions. Example 3 achieved the highest hardness due to a higher rare earth content and higher temperature, but its corrosion resistance was slightly lower than that of Example 1. This indicates that the proportion range and process parameters defined in this invention can balance hardness and corrosion resistance according to actual needs.
[0029] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0030] The above description is merely an example and illustration of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.
Claims
1. An environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts, characterized in that, Includes the following steps: (1) The surface of the mining support anchor bolt is subjected to acid-free mechanical rust removal treatment to achieve a surface cleanliness of Sa2.5 or higher and a roughness Rz controlled at 25-75 μm; (2) The rust-removed anchor bolt is mixed with a chromium-free rare earth infiltration agent and then placed in a sealed zinc infiltration container. The chromium-free rare earth infiltration agent is composed of the following components by mass percentage: 85%-95% zinc powder, 1%-4% activator, 3%-11% anti-caking agent, and 0.5%-2% rare earth infiltration agent. The agent is a mixture of cerium chloride and lanthanum chloride, wherein the mass ratio of cerium chloride to lanthanum chloride is 1:(0.5-2); (3) The zinc diffusion container is heated at a temperature of 340-440℃ and continuously rotated for 2-6 hours to make the anchor rod fully contact the zinc diffusion agent and form a zinc-iron alloy diffusion layer on the surface of the anchor rod; (4) After zinc diffusion is completed, the anchor rod is cooled to room temperature, the anchor rod and the residual zinc diffusion agent are separated, and the surface of the anchor rod is dry cleaned to obtain a mining support anchor rod with a corrosion-resistant zinc diffusion layer.
2. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, The mechanical rust removal described in step (1) is sandblasting or shot blasting, and the process is carried out in a fully enclosed negative pressure dust removal system.
3. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, The activator in step (2) is ammonium chloride, and the anti-caking agent is aluminum oxide.
4. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, The zinc powder mentioned in step (2) has a particle size of 200-400 mesh and a purity of not less than 99%.
5. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, In step (3), the heating rate is 5-10℃ / min and the container rotation speed is 3-8r / min.
6. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, The dry cleaning described in step (4) involves blowing with compressed air and then applying a polishing brush.
7. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, The base material of the mining support anchor is Q235, Q345, 20MnSi or 25MnSi steel.
8. The environmentally friendly treatment process for corrosion-resistant zinc-impregnated surface treatment of mine support anchor bolts according to claim 1, characterized in that, The thickness of the zinc-impregnated anti-corrosion layer is 25-80 μm.